(untitled) (American Journal of Business Management, Economics and Banking, 2023)
In this article, the French philology students to work on specialized texts of various teaching about the use of appropriate technologies to specialized. The way to work on strengthening students the knowledge and skills of the Uzbek language, specialties within the framework of language learning.